Occurrences, spatial distributions, and ecological risks of organic ultraviolet absorbents in surface sediments from Taihu Lake, China - Wen Gu; Shuai Sun; Yinying Cai; Ziyan Du; Xiaohan Shan; Mengyuan Liang; Min Guo; Linjun Zhou; Yong Zhang (Emerging Contaminants)
The occurrences and spatial distributions of eight organic ultraviolet absorbents (UVAs) were investigated in surface sediments from Taihu Lake, China. The detection frequencies and concentrations of UVAs in 2016 were significantly higher than those in 2015.2-Ethylhexyl methoxycinnamate and homosalate (HMS) were the predominant UVAs in the sediment samples. The total UVA concentration range in sediment samples was 0.15–85.3 ng/g. The spatial distribution results showed that UVAs were concentrated in the northwest of Taihu Lake. The total organic carbon content may affect the fate of UVAs in sediments. Source analysis and correlation analysis showed that the following compounds had high proportions and significant correlations: 2-ethylhexyl methoxycinnamate, ethylhexyl salicylate, and HMS in 2015; and benzophenone-3, HMS, and benzyl salicylate in 2016. These results indicated the correlated compounds within each year had the same source. Ecological risk assessment results showed that UVAs in sediment from Taihu Lake may present a moderate risk to benthic organisms. The risk quotient of UVAs in 2016 was slightly higher than that in 2015. The seasonal pollution characteristics of UVAs and their comprehensive environmental risks should receive further attention.